EP940 Chemokine expression in patients with ovarian cancer or benign ovarian tumors. (1st November 2019) - Nowak, M; Janas, Ł; Soja, M; Głowacka, E; Szyłło, K; Misiek, M; Klink, M
Abstract : Introduction/Background: Chemokines play a crucial role in tumor growth and progression according to proangiogenic and immunosuppressive acting. This study was aimed to investigate the serum levels of selected chemokines in patients with ovarian cancer or benign ovarian tumors to point on their role in tumorigenesis and the potential use in preoperative diagnosing of adnexal mass. Methodology: The study group consisted of 59 women: 17 epithelial ovarian cancer (EOC) patients (7 in early and 10 in advanced stage) and 42 with benign ovarian tumors (12 endometriotic and 30 other epithelial). We measured in sera obtained preoperatively the level of CA125 and the panel of 5 chemokines: CX3CL1/Fractalkine, CXCL1/GRO-α, CXCL12/SDF-1, CCL20/MIP-3α and IL-17F, using chemiluminescence method with multiplexed bead based immunoassay. Results: CX3CL1 was significantly elevated in sera of ovarian cancer patients compared to women with benign ovarian tumors (13, 3±7, 9 pg/ml vs 6, 7±3, 0 pg/ml, p<0, 005). When FIGO stage was taken into consideration we found that only advanced cancer patients showed significantly higher concentrations. The significant elevation of CXCL1, both in early and advanced stage of cancer vs benign tumors was also observed (36, 5±18, 4 pg/ml vs 17, 6±8, 7 pg/ml, p<0, 01). The similar pattern was present with standard ovarian cancer marker - CA125. In our patients with endometriotic cysts CA125 levels were also significantly higher than in women with other benign tumors whereas both mentioned above chemokines had similar serum titers in patients with endometriotic vs other benign ovarian cysts. Conclusion: CX3CL1 and CXCL1 are elevated in sera of EOC patients what points on their role in cancer development. Moreover, they might be useful in preoperative differential diagnosis of ovarian tumors, especially as they were not elevated in cases of endometriosis. Disclosure: Nothing to disclose.